Studi Literatur Generasi Lemah dan Peran Pendidikan Agama dalam QS. An-Nisa: 9 - Amrul Fajrin Marundruri (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
This study aims to analyse the word of Allah in Qs. An-Nisa: 9 about the weak generation information and the solution in the verse. This research uses a literature review by reviewing appropriate documents to produce an in-depth study. The results of the study found that the younger generation has a lot of challenges and obstacles both internally and externally, such as mental illness, easy stress, drug promiscuity and so on. All of this will provide opportunities for the weakening of the generation so that the potential for the decline of the generation on a quality scale is enormous. If seen in Qs. An-Nisa: 9 has informed far - far away, and with today's facts, it can be stated as trustworthy so that this vital information can provide anticipation for the older generation and all its components to participate in breaking this and trying to print a strong and quality young generation so that the impact will not only be felt by them today but for future generations